Self-adhesion-crosslinking double modified bamboo powder as well as preparation method and application thereof
Through the self-adhesion-crosslinking dual modification method, the interface compatibility and crystallinity of PBAT and bamboo powder are enhanced, and the problem of degradation of PBAT/bamboo powder composite material is solved, achieving high-performance and environmentally friendly modification effect.
Patent Information
- Application Number
- CN202510679076.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-26
- Publication Date
- 2025-07-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing modification methods are difficult to effectively improve the interface compatibility and mechanical properties of PBAT and bamboo powder, resulting in a decline in the performance of composite materials. The traditional modification process is not environmentally friendly or complex, resulting in the problem of "three wastes".
The self-adhesion-crosslinking dual modification method was adopted to react with bamboo powder by reacting substances such as 2,5-dihydroxyterephthalic acid, 4-aminobenzohydrazide, N,N'-diisopropylcarbodiimide and trimethylolamide to form a self-adhesion-crosslinking network to enhance the interface compatibility and crystallinity of bamboo powder and PBAT.
It improves the mechanical properties and interface compatibility of PBAT/bamboo powder composite materials, reduces the surface polarity of bamboo powder, improves the comprehensive performance of the material, and realizes a green and environmentally friendly modification process.
Smart Images

Figure CN120230312A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and particularly to self-adhesive-crosslinked dual-modified bamboo powder, a preparation method and an application thereof. Background Art
[0002] With the increasing environmental protection requirements, traditional dust-proof nets prepared from raw materials such as polyethylene and polypropylene have aggravated the "white pollution" due to their non-degradability and long-term accumulation in the environment after use. Therefore, the development of degradable alternatives has become an urgent need. Poly(butylene adipate-co-terephthalate) (PBAT), as a degradable polyester, has good biodegradability and processing properties and has become a preferred material for preparing degradable dust-proof nets. However, the dust-proof nets made of PBAT have disadvantages such as high cost and insufficient hydrophilicity, which limit their practical applications. Bamboo powder, as a natural renewable resource, has advantages such as wide sources and low cost. Adding it to PBAT is expected to improve the material properties and reduce the cost. However, there are a large number of hydroxyl groups on the surface of bamboo powder, which have strong polarity and hydrophilicity and poor compatibility with the PBAT matrix, resulting in weak interfacial bonding force of the composite material and easy phase separation, thereby affecting the comprehensive performance of the dust-proof net. Therefore, it is necessary to modify bamboo powder to form a good interfacial bond with PBAT, which is of great significance for preparing low-cost and high-performance degradable PBAT dust-proof nets.
[0003] Currently, for the modification treatment of bamboo powder, the main methods include esterification modification of bamboo powder and hydrophobic modification of bamboo powder by adding modifiers. For example, using PEW-g-MAH to esterify bamboo powder can reduce the hydroxyl group content on the surface of bamboo powder and improve its hydrophobicity. However, such esterification auxiliaries have problems such as uneven dispersion and inability to effectively enhance the mechanical properties of PBAT / bamboo powder. Another example is to use NaOH solution and γ-aminopropyltriethoxysilane to synergistically modify bamboo powder. After being treated with NaOH solution, the crystallinity of bamboo powder increases. After further modification with γ-aminopropyltriethoxysilane, low surface energy Si-CH3 groups are introduced on the surface of bamboo powder, turning bamboo powder from hydrophilic to hydrophobic, thereby improving the compatibility between bamboo powder and PBAT. However, the alkali treatment modification process is cumbersome and complex, which is not conducive to the coherence of the production process. At the same time, it will also cause the problem of "three wastes", which is extremely unfavorable to industrial production. Therefore, it is urgent to develop a green and environmentally friendly modified bamboo powder that can improve the interfacial compatibility between PBAT and bamboo powder and enhance the properties of PBAT / bamboo powder composites. Summary of the Invention
[0004] Based on the technical problems existing in the background art, the present invention provides a self-adhesive cross-linked double-modified bamboo powder, a preparation method and an application thereof. The modified bamboo powder is green and environmentally friendly. Through self-adhesive mechanism, cross-linking mechanism and branched phenyl heterogeneous nucleation mechanism, etc., the interfacial compatibility between PBAT and bamboo powder and the crystallinity of PBAT are improved, thereby enhancing the mechanical properties of PBAT / bamboo powder.
[0005] A preparation method of a self-adhesive cross-linked double-modified bamboo powder provided by the present invention comprises the following steps:
[0006] S1: Mix bamboo powder, 2,5-dihydroxyterephthalic acid, 4-aminobenzohydrazide, N,N'-diisopropylcarbodiimide and tris(hydroxymethyl)aminomethane for reaction;
[0007] S2: Add trimellitic acid to the solution after the reaction in S1 for reaction, and after filtration, washing and drying, a self-adhesive cross-linked double-modified bamboo powder is obtained.
[0008] Preferably, the mass ratio of bamboo powder, 2,5-dihydroxyterephthalic acid, 4-aminobenzohydrazide, N,N'-diisopropylcarbodiimide and trimellitic acid is 150:1-2:0.5-2:0.5-1.5:2-5.
[0009] Preferably, in S1, tris(hydroxymethyl)aminomethane is added to control the pH of the reaction system to 8-9.
[0010] Preferably, the reaction conditions in S1 are: stirring speed 300-400 rpm, temperature 50-80 °C, time 12-16 h.
[0011] Preferably, the reaction conditions in S2 are: stirring speed 300-400 rpm, temperature 110-130 °C, time 8-12 h.
[0012] A self-adhesive cross-linked double-modified bamboo powder provided by the present invention is prepared by the above preparation method.
[0013] A preparation method of a PBAT / bamboo powder dust-proof net provided by the present invention comprises the following steps: Mix poly(butylene adipate-co-terephthalate) and the above self-adhesive cross-linked double-modified bamboo powder by high-speed mixing, melt extrusion, cooling, pelletizing, blowing, wire drawing and weaving to obtain a PBAT / bamboo powder dust-proof net.
[0014] Preferably, the mass ratio of poly(butylene adipate-co-terephthalate) and self-adhesive cross-linked double-modified bamboo powder is 1:0-1.
[0015] Preferably, the melt extrusion conditions are as follows: the screw speed is 200 - 300 rpm, the feeding speed is 3 - 5 Hz, and the extrusion temperature zones are set at 120, 120, 120, 125, 125, 125, 130, 130, 130, 125, 125, 125 °C.
[0016] Advantageous technical effects of the present invention:
[0017] (1) The modification process of the modified bamboo powder PDAT - BF prepared by the present invention is green and environmentally friendly. The in - situ liquid phase method is used for the reaction, so that the modifier is uniformly dispersed and coated on the surface of the bamboo powder, thereby reducing the surface polarity of the bamboo powder, improving the compatibility between the bamboo powder and PBAT, and the mechanical properties of the PBAT / bamboo powder.
[0018] (2) For the PDAT - BF prepared by the present invention, a quaternary system with 2,5 - dihydroxyterephthalic acid, 4 - aminobenzohydrazide, trimesic acid and bamboo powder as polymerization monomers is established. Through the synergistic effect of the chemical cross - linking and hydrogen - bond cross - linking networks, the interaction force between the bamboo powder and PBAT is enhanced, and thus the mechanical properties of the PBAT / bamboo powder are improved.
[0019] (3) For the PDAT - BF prepared by the present invention, phenol - based and amine - based substances are used as the main chain monomers of the polymerization. By generating self - adhesion, the interaction force between the modifier, bamboo powder and PBAT is enhanced, and thus the mechanical properties of the PBAT / bamboo powder are improved.
[0020] (4) For the PDAT - BF prepared by the present invention, through the heterogeneous nucleation effect of the branched benzene ring and the dipole - dipole (N - H···O = C) interaction between the hydrazide group and the PBAT molecule, the crystallization of PBAT on the surface of the bamboo powder is promoted, thereby enhancing the mechanical properties of the PBAT / bamboo powder. Description of the Drawings
[0021] Figure 1 It is the FT - IR comparison diagram of BF and PDAT - BF - 2 proposed by the present invention;
[0022] Figure 2 It is the crystallization / melting curve comparison diagram of PBAT, PBAT / BF - 4 and PBAT / PDAT - BF - 2 proposed by the present invention; among them, (a) is the cooling crystallization process, and (b) is the heating melting process;
[0023] Figure 3 It is the synthesis route diagram of PDAT - BF proposed by the present invention;
[0024] Figure 4 It is the self - adhesion mechanism diagram of PDAT - BF proposed by the present invention, where (a) is the hydrogen - bond interaction, (b) is the ionic - bond interaction, (c) is the π - π stacking interaction, and (d) is the cation - π interaction;
[0025] Figure 5 This is the compatibility, crystallization and cross-linking mechanism diagram of PBAT / PDAT-BF proposed by the present invention. Specific embodiments
[0026] The present invention will be further explained below in conjunction with specific embodiments.
[0027] In the embodiments of the present invention, bamboo powder (600-1000 mesh), 2,5-dihydroxyterephthalic acid (DHTA), 4-aminobenzohydrazide (AH), N,N'-diisopropylcarbodiimide (DIC), trimesic acid (TMA), tris(hydroxymethyl)aminomethane (Tris), etc. are all commercially available.
[0028] In the embodiments of the present invention, the melt index (190 °C, 2.16 kg) of PBAT is 3.42 g / 10 min, the melting point is 111.87 °C, and the carboxyl content is 13.27 mol / t.
[0029] Example 1
[0030] Weigh 300 g of dried bamboo powder (BF) and suspend it in 2000 g of distilled water, stir evenly to prepare a bamboo powder suspension. Then, add tris(hydroxymethyl)aminomethane (Tris) dropwise to the bamboo powder suspension, and control the pH of the bamboo powder suspension to be about 8.5. Secondly, weigh 2 g of 2,5-dihydroxyterephthalic acid (DHTA), 1.2 g of N,N'-diisopropylcarbodiimide (DIC) and 1.4 g of 4-aminobenzohydrazide (AH) respectively, and add them to the bamboo powder suspension in sequence to obtain a mixed solution. Finally, transfer the obtained mixed solution to a reaction kettle and react at 300 rpm and 60 °C for 12 h to obtain a suspension, denoted as PDA-BF-1.
[0031] Weigh 4.2 g of trimesic acid (TMA) in 400 g of distilled water and ultrasonically dissolve it until completely dissolved. Subsequently, add the trimesic acid solution to the above suspension PDA-BF-1 and heat up and react at 300 rpm and 110 °C for 8 h. After the reaction is completed, cool and stand to obtain a suspension. Add the suspension to a vacuum filter for filtration, and at the same time wash it with distilled water until the filtrate is neutral, and then place the obtained solid in an oven at 80 °C and dry it for 12 h to obtain the product, denoted as PDAT-BF-1.
[0032] Weigh 0.8 kg of PBAT and 0.2 kg of PDAT-BF-1, and conduct high-speed mixing to obtain a mixed material; melt-extrude the mixed material, set the screw speed to 200 rpm, the feeding speed to 3 Hz, and the extrusion temperature zones to 120, 120, 120, 125, 125, 125, 130, 130, 130, 125, 125, 125 °C to obtain a composite material, denoted as PBAT / PDAT-BF-1. The composite material is cooled, pelletized, blown into a film, cut into filaments, and woven to obtain a PBAT / bamboo powder dust-proof net.
[0033] Example 2
[0034] Weigh 6.2 g of TMA into 400 g of distilled water and ultrasonically dissolve it until completely dissolved. Subsequently, add the trimesic acid solution to the suspension PDA-BF-1, and carry out a temperature-raising reaction at 300 rpm and 110 °C for 8 h. After the reaction is completed, cool and let it stand to obtain a suspension. Add the suspension to a vacuum filter for filtration, and at the same time wash it with distilled water until the filtrate is neutral. Then place the obtained solid in an 80 °C oven and dry it for 12 h to obtain the product, denoted as PDAT-BF-2.
[0035] Weigh 0.8 kg of PBAT and 0.2 kg of PDAT-BF-2, and conduct high-speed mixing to obtain a mixed material; melt-extrude the mixed material, set the screw speed to 200 rpm, the feeding speed to 3 Hz, and the extrusion temperature zones to 120, 120, 120, 125, 125, 125, 130, 130, 130, 125, 125, 125 °C to obtain a composite material, denoted as PBAT / PDAT-BF-2. The composite material is cooled, pelletized, blown into a film, cut into filaments, and woven to obtain a PBAT / bamboo powder dust-proof net.
[0036] Example 3
[0037] Weigh 8.2 g of TMA into 400 g of distilled water and ultrasonically dissolve it until completely dissolved. Subsequently, add the trimesic acid solution to the suspension PDA-BF-1, and carry out a temperature-raising reaction at 300 rpm and 110 °C for 8 h. After the reaction is completed, cool and let it stand to obtain a suspension. Add the suspension to a vacuum filter for filtration, and at the same time wash it with distilled water until the filtrate is neutral. Then place the obtained solid in an 80 °C oven and dry it for 12 h to obtain the product, denoted as PDAT-BF-3.
[0038] Weigh 0.8 kg of PBAT and 0.2 kg of PDAT-BF-3, and perform high-speed mixing to obtain a mixed material; melt-extrude the mixed material, set the screw speed to 200 rpm, the feeding speed to 3 Hz, and the extrusion temperature zones to 120, 120, 120, 125, 125, 125, 130, 130, 130, 125, 125, 125 °C to obtain a composite material, denoted as PBAT / PDAT-BF-3. The composite material is cooled, pelletized, blown into a film, cut into filaments, and woven to obtain a PBAT / bamboo powder dust-proof net.
[0039] Comparative Example 1
[0040] Weigh 0.8 kg of PBAT and 0.2 kg of BF, and perform high-speed mixing to obtain a mixed material; melt-extrude the mixed material, set the screw speed to 200 rpm, the feeding speed to 3 Hz, and the extrusion temperature zones to 120, 120, 120, 125, 125, 125, 130, 130, 130, 125, 125, 125 °C to obtain a composite material, denoted as PBAT / BF-4. The composite material is cooled, pelletized, blown into a film, cut into filaments, and woven to obtain a PBAT / bamboo powder dust-proof net.
[0041] Comparative Example 2
[0042] Add the suspension PDA-BF-1 to a vacuum filter for filtration, and at the same time wash with distilled water until the filtrate is neutral. Then place the obtained solid in an 80 °C oven and dry for 12 h to obtain a dried product; then weigh 0.8 kg of PBAT and 0.2 kg of the above dried product and perform high-speed mixing to obtain a mixed material; melt-extrude the mixed material, set the screw speed to 200 rpm, the feeding speed to 3 Hz, and the extrusion temperature zones to 120, 120, 120, 125, 125, 125, 130, 130, 130, 125, 125, 125 °C to obtain a composite material, denoted as PBAT / PDA-BF-1. The composite material is cooled, pelletized, blown into a film, cut into filaments, and woven to obtain a PBAT / bamboo powder dust-proof net.
[0043] Comparative Example 3
[0044] First, weigh 300 g of dried BF and suspend it in 2000 g of distilled water, stir evenly to prepare a bamboo powder suspension. Then, weigh 6.2 g of TMA in 400 g of distilled water and ultrasonically dissolve it until completely dissolved. Subsequently, add the solution of trimesic acid to the above bamboo powder suspension, and raise the temperature and react for 8 h under the conditions of 300 rpm and 110 °C. After the reaction is completed, cool and let it stand to obtain a suspension. Add the suspension to a vacuum filter, filter and wash to obtain a wet solid, and then place the obtained wet solid in an 80 °C oven and dry for 12 h to obtain the product, denoted as T-BF.
[0045] Weigh 0.8 kg of PBAT and 0.2 kg of T-BF, and perform high-speed mixing to obtain a mixed material; melt-extrude the mixed material, set the screw speed to 200 rpm, the feeding speed to 3 Hz, and the extrusion temperature zones to 120, 120, 120, 125, 125, 125, 130, 130, 130, 125, 125, 125 °C to obtain a composite material, denoted as PBAT / T-BF. The composite material is cooled, pelletized, blown into a film, cut into filaments, and woven to obtain a PBAT / bamboo powder dust-proof net.
[0046] Perform mechanical property tests on the monofilament film samples of PBAT, Examples 1-3, and Comparative Examples 1-3. The test standard is carried out in accordance with GB / T 1040.1-2018 "Determination of Tensile Properties of Plastics - Part 1: General Principles". The results are shown in Table 1.
[0047] Table 1 Mechanical Property Tests
[0048] As can be seen from Table 1, the mechanical properties of the pure PBAT sample are the highest, and the mechanical properties decrease significantly after filling with unmodified bamboo powder. Among the samples filled with modified bamboo powder, the sample prepared by Example 2 has the best mechanical properties, with a tensile strength of 21.94 Mpa and an elongation at break of 487%. The reason for the above phenomenon is that when PBAT is directly blended with unmodified bamboo powder, due to the poor interfacial compatibility between PBAT and unmodified bamboo powder, stress concentration and crack phenomena occur during the stretching process of the monofilament film, so the mechanical properties decrease significantly. However, when modified bamboo powder is added, the tensile strength of the film is significantly improved. The reason is that the modified bamboo powder enhances the intermolecular force in the PBAT / bamboo powder system through self-adhesion and the construction of a cross-linked network, and promotes the crystallization of PBAT through the heterogeneous nucleation mechanism and the interaction between the hydrazide group and PBAT, thereby improving the compatibility between PBAT and bamboo powder and the tensile strength of the PBAT / bamboo powder system. Further analysis shows that when trimellitic acid is not added, the modified bamboo powder only enhances the intermolecular force in the PBAT / bamboo powder system through self-adhesion and hydrogen bond interaction, thereby improving the tensile strength of the PBAT / bamboo powder system; when only trimellitic acid is added, the modified bamboo powder only improves the tensile strength of the PBAT / bamboo powder system through micro-crosslinking between bamboo powders, and no cross-linked network is generated; compared with the present invention, the above situations will reduce the intermolecular force in the PBAT / bamboo powder system, and thus reduce the tensile strength of the PBAT / bamboo powder system.
[0049] The present invention performs infrared tests on BF and PDAT-BF-2 samples, and the results are as Figure 1 shown. From Figure 1It can be seen that compared with pure BF, the peak at 3342 cm -1 of PDAT-BF-2 is the stretching vibration peak of O-H; the peak appearing at 1917 cm -1 is the overtone peak of trisubstituted benzene; the peaks at 888 cm -1 , 819 cm -1 and 663 cm -1 are the characteristic peaks of trisubstituted benzene; the peak at 1108 cm -1 is the stretching vibration peak of C-O-C in the ester group; the peak intensity of the C=O peak increases at 1724 cm -1 ; the peaks at 1724 cm -1 , 1627 cm -1 and 1418 cm -1 are the band Ⅰ, band Ⅱ and band Ⅲ of the amide group respectively. Among them, the peak at 1418 cm -1 is the stretching vibration peak of C-N. Thus, it can be known that 2,5-dihydroxyterephthalic acid, 4-aminobenzohydrazide and trimesic acid have been successfully reacted onto bamboo powder.
[0050] Differential scanning calorimetry tests were carried out on PBAT samples, PBAT / BF-4 and PBAT / PDAT-BF-2 in this invention, and the results are as Figure 2 shown, where (a) is the cooling crystallization process and (b) is the heating melting process. The details of the thermodynamic parameters of the samples are shown in Table 2.
[0051] Table 2 Thermodynamic parameters of the samples
[0052] From Figure 2 and Table 2, it can be seen that pure PBAT shows an obvious exothermic peak curve, and a strong melting crystallization peak is observed at 35.43 °C. With the addition of BF-4 and PDAT-BF-2, the melting temperature and crystallization temperature of PBAT increase, indicating that these two fillers promote the crystallization of PBAT. Among them, the crystallization temperature of PBAT / PDAT-BF-2 reaches 59.78 °C, and the crystallization effect is the best. This is because PDAT-BF-2 stimulates the heterogeneous nucleation of the surface side-chain phenyl groups through hydrogen bond interaction, and at the same time promotes the crystallization of PBAT on the surface of bamboo powder through the dipole-dipole interaction between the surface self-adhesive hydrazide groups and the carbonyl groups in PBAT. In addition, PBAT shows a glass transition at about -31.75 °C, and then a melting peak at 120.77 °C. After adding BF-4 and PDAT-BF-2, the T g and T m of the composite materials both shift towards higher temperatures. T gThe increase indicates that since PDAT-BF-2 has good compatibility with PBAT, as a rigid material, it restricts the movement of PBAT molecular chains; T m The increase indicates that the interaction between PDAT-BF-2 molecules and PBAT molecular chains is stronger, and the heat resistance of the material is improved.
[0053] It can also be seen from the thermodynamic parameters in Table 2 that PBAT / PDAT-BF-2 has a higher ∆H m than PBAT / BF-4, and PBAT / PDAT-BF-2 has a higher crystallinity. This is because the modified PDAT-BF-2 enhances its binding ability with PBAT through various nucleation mechanisms and interfacial interactions.
[0054] Figure 4 is the self-adhesion mechanism diagram of PDAT-BF proposed by the present invention. PDAT-BF enhances the interaction forces among the modifier, bamboo powder, and PBAT by generating four interaction forces: hydrogen bonds, ionic bonds, π-π stacking, and cation-π interactions, thereby improving the mechanical properties of the PBAT / bamboo powder composite. Figure 5 is the compatibility, crystallization, and crosslinking mechanism diagram of PBAT / PDAT-BF proposed by the present invention. The trimellitic acid in the side chain of the modifier of the present invention contains multiple carboxyl functional groups, and crosslinks the bamboo powder and PBAT through esterification reaction and hydrogen bond interaction. In addition, after the modifier fixes PBAT through hydrogen bonds, the phenyl group (hard segment) in trimellitic acid generates heterogeneous nucleation to promote the crystallization of PBAT; the hydrazide group in the main chain further induces crystallization through the dipole-dipole interaction with the carbonyl group of PBAT. At the same time, the modifier reduces the hydroxyl content on the surface of the bamboo powder through chemical reactions and hydrogen bond interactions, and bridges the bamboo powder and PBAT, thereby improving their compatibility.
[0055] Although the embodiments of the present application have been shown and described, for those of ordinary skill in the art, it can be understood that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirits of the present application. The scope of the present application is defined by the appended claims and their equivalents, and all should be included within the protection scope of the present application.
Claims
1. A preparation method of self-adhesive and cross-linked double-modified bamboo powder, characterized in that, The method steps are as follows: S1: Mix bamboo powder, 2,5-dihydroxyterephthalic acid, 4-aminobenzohydrazide, N,N'-diisopropylcarbodiimide and tris(hydroxymethyl)aminomethane for reaction; S2: Add trimellitic acid to the solution after the reaction in S1 for reaction, and obtain self-adhesive-crosslinked double-modified bamboo powder through filtration, washing and drying.
2. The preparation method of the self-adhesive and cross-linked double-modified bamboo powder according to claim 1, wherein The mass ratio of bamboo powder, 2,5-dihydroxyterephthalic acid, 4-aminobenzohydrazide, N,N'-diisopropylcarbodiimide and trimellitic acid is 150:1-2:0.5-2:0.5-1.5:2-5.
3. The preparation method of the self-adhesive cross-linked double-modified bamboo powder according to claim 1, characterized in that, In S1, tris(hydroxymethyl)aminomethane is added to control the pH of the reaction system to 8-9.
4. The preparation method of the self-adhesive and cross-linked double-modified bamboo powder according to claim 1, characterized in that, The reaction conditions in S1 are: stirring speed 300-400 rpm, temperature 50-80 °C, time 12-16 h.
5. The preparation method of the self-adhesive and cross-linked double-modified bamboo powder according to claim 1, characterized in that, The reaction conditions in S2 are: stirring speed 300-400 rpm, temperature 110-130 °C, time 8-12 h.
6. A self-adhesive-crosslinked double-modified bamboo powder, characterized in that, Prepared by the preparation method described in any one of claims 1-5.
7. A preparation method of a PBAT / bamboo powder dust-proof net, characterized in that, The method steps are as follows: Poly(butylene adipate-co-terephthalate) and the self-adhesive-crosslinked double-modified bamboo powder described in claim 6 are subjected to high-speed mixing, melt extrusion, cooling, pelletizing, blown film, wire drawing and weaving to obtain a PBAT / bamboo powder dust-proof net.
8. The preparation method of the PBAT / bamboo powder dust-proof net according to claim 7, characterized in that, The mass ratio of poly(butylene adipate-co-terephthalate) and self-adhesive-crosslinked double-modified bamboo powder is 1:0-1.
9. The preparation method of the PBAT / bamboo powder dust-proof net according to claim 7, characterized in that, The melt extrusion conditions are: screw speed 200-300 rpm, feeding speed 3-5 Hz, and the extrusion temperature zones are set at 120, 120, 120, 125, 125, 125, 130, 130, 130, 125, 125, 125 °C.
Citation Information
Patent Citations
Bamboo powder filled biomass-based resin composite material and preparation method thereof
CN101602882A
Degradable bamboo fiber PBAT material and film preparation method
CN118256069A
Cited By
Preparation of bi-crosslinking network synergistically modified PBAT-KT-BF composite material and application of composite material in dustproof net
CN120988316A
Preparation of PBAT-KT-BF composite modified by double crosslinking network and its application in dust screen
CN120988316B
Bamboo powder reinforced polypropylene composite fiber for concrete crack resistance and preparation method of bamboo powder reinforced polypropylene composite fiber
CN121781302A